Pencegahan Investasi Bodong Dengan Pengenalan Instrumen Pasar Modal Sebagai Alternatif Investasi Bagi Generasi Z - M Iqbal Harori; Nindya Eka Sobita; Iqrima Aini; Rendy Satya Aji Paluvi (Yayasan Daarul Huda Kruengmane, 2023)
Cases of fraudulent investment or chain arisan in Indonesia have now been uncovered not only attacking big cities, but have penetrated into villages. So educating the public by making the right and legal investments is a must. If you look at the current century and developments, it's a shame that many people are still deceived by the lure of investments that promise wealth in a short time, with all the ease of access to information at this time, but in fact in Lampung in 2022 the police reveal that the catch from fraudulent investments has reached 66 billion rupiah, and that was money that was collected from 620 people, and it turned out that it was not only the people who were deceived who had weak economic capabilities, but even those who were highly educated, while their hope was to be able to improve their family's economic conditions. This service aims to provide socialization and introduction to the Capital Market as an investment instrument that is legal and supervised by the OJK for generation Z who can be the first deterrents in the family. The method used is to give seminars and discussions. To overcome the problems faced by people who are unfamiliar with investment. This training is the right solution for the problems faced by the community. The long-term target to be achieved in this activity is to make Generation Z understand about legal investments and avoid fraudulent investments.